Effects of chronic fluoride toxicity on the morphology of ductus epididymis and the maturation of spermatozoa of rabbit. - Kumar, A. (1995)
This study used light and scanning electron microscopy to observe the effect of chronic fluoride toxicity on the structure of the ductus epididymis, testis and spermatozoa in rabbit. The rabbits were treated with 10 mg NaF/kg body weight/day for 20 and 23 months. Serum fluoride was estimated by the fluoride ion-specific electrode method. Fluoride levels in the sera of both 20 and 23-month treated rabbits were significantly increased (P < 0.001). Loss of stereocilia, significant decrease (P < 0.001) in the height of the pseudostratified columnar epithelium and significant increase (P < 0.001) in the diameter of both the caput and cauda ductus epididymis were observed only in the 23-month fluoride treated rabbits. The decreases in the epithelial cell height (P < 0.01) and the tubular diameter (P < 0.001) of the testis were significant only in 23-month treated animals. Spermatozoa in the lumen of the testis of both treated groups of animals and in the caput and cauda ductus epididymis of 20-month treated animals appeared normal, but spermatozoa in the caput and cauda ductus epididymis of 23-month treated animals were fragmented. In the 23-month fluoride treated rabbits, the weights of the caput and cauda epididymis were significantly reduced (P < 0.025) and there was also a reduction in the number of secretory granules in these organs. The structural changes observed in the caput and cauda ductus epididymis might adversely affect the maturation of spermatozoa.